Kompetensi Guru Dalam Perspektif Jalaluddin Abdurrahman As- Suyuthi - Yulianto, Ahmad; Zakiyah, Millatuz (AL-WIJDÃN Journal of Islamic Education Studies, 2017)
Teacher is one crucial part of the teaching and learning process. Consequently, a competent teacher is important to achieve an ideal learning outcome. Al-Suyuti, a well versed expert in Hadith, asserts special skills that a teacher should possess. This research analyzed (1) the teacher’s competency model by Al-Suyuti and (2) educational competence, personal competence, social competence, and professional competence according to Al-Suyuti. This research used an analytical descriptive method. The results of research show that according to Al-Suyuti, teachers should have good manners, and correct intentions, reach the age of accountability, dress accordingly, use a good teaching method, teach based on students’ skills and age, understand students’ circumstances, be humble, and implement fair and reliable assessments. Later, each competency is classified based on pedagogic competence, personal competence, social competence, and professional competence. Keywords: Al-Suyuti, competence, pedagogic, personal, social, and professional.